Breakthroughs in Perovskite Solar Cells: Advancing Efficiency and Stability for Next-Generation Photovoltaics - Chetan, Anjna (Journal for Research in Applied Sciences and Biotechnology, 2022)
Perovskite solar cells (PSCs) have emerged as a revolutionary technology in photovoltaics, demonstrating rapid progress and potential for transforming solar energy generation. This paper delves into the latest breakthroughs in PSCs, focusing on enhancing efficiency and stability for next-generation photovoltaics. We trace the evolution of PSCs from their inception in 2009, where initial power conversion efficiencies (PCEs) were 3.8%, to recent advancements surpassing 25%. Key advantages of PSCs, such as low-temperature solution-based fabrication and the potential for flexible, lightweight solar panels, are discussed. Our research is structured around five main objectives: first, investigating advances in perovskite materials, particularly mixed cations and anions that enhance efficiency and stability. Second, exploring strategies to boost efficiency through advanced light management, optimized charge transport layers, and improved interface engineering. Third, addressing stability by developing robust encapsulation techniques and moisture-resistant materials, alongside optimizing thermal and photostability. Fourth, assessing innovative device architectures like tandem solar cells and flexible, lightweight designs for diverse applications. Fifth, examining the scalability of PSC production, including manufacturing challenges, cost analysis, and market potential. By addressing these objectives, the paper provides a comprehensive overview of current PSC technology and identifies key areas for future development, aiming to advance PSCs as a viable, sustainable solution for global energy needs.